Taxation of digital financial assets in the context of classical rules of taxation - K. A. Ponomareva; A. O. Simonov (Правоприменение, 2024)
Subject. The existing mechanisms of taxation of transactions with crypto assets on the territory of the Russian Federation are analyzed in the article. The choice of the research object is due to the increasing role of crypto assets in the modern Russian economy, as well as the necessity to propose new mechanisms to ensure the tax security of the state in the face of new challenges.The purpose of the study. The existing mechanisms of taxation of transactions related to the use and turnover of crypto assets in Russia are considered. Authors analyze both the main problems faced by individuals and legal entities operating with cryptocurrencies. The analysis of the current legislation is provided, possible ways to improve the legislation are suggested.Methodology. In the course of their work, the researchers were guided by philological and systematic ways of interpreting current legal norms, as well as existing explanations of financial authorities related to current approaches to taxation of transactions with crypto assets.Conclusions. It is concluded that the approaches proposed by the legislator to taxation of transactions with crypto assets are similar to the mechanisms that apply to traditional financial instruments, but at the same time, assets that are not similar to traditional ones remain outside the regulation.